The T1799A BRAF mutation is not a germline mutation in familial nonmedullary thyroid cancer - Xing, Mingzhao (Clinical endocrinology (Oxford), 2005)
Summary Objective  Familial nonmedullary thyroid cancer (FNMTC) is relatively common but its predisposing genetic alteration is unclear. As the somatic T1799A BRAF mutation is highly prevalent in papillary thyroid cancer, the aim was to test whether this mutation was a susceptibility mutation for FNMTC. Subjects and methods  The T1799A BRAF mutation as a possible germline mutation was examined in 40 subjects from 23 families with a history of FNMTC. Direct DNA sequencing was performed on white blood cell DNA samples to analyse the mutation status. Results  No T1799A BRAF mutation was found in this group of subjects as germline mutation. Conclusion  The T1799A BRAF mutation is not a germline mutation or susceptibility genetic event for FNMTC.